2014
DOI: 10.1017/s095026881400332x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in swine co-infected withMycobacterium aviumsubsp.hominissuisandMycobacterium bovisin a cluster from Argentina

Abstract: SUMMARY In Argentina little is known about the epidemiology of tuberculosis (TB) infection in swine. We characterized the epidemiological dynamics of Mycobacterium avium complex (MAC) infection in a swine population of Argentina using molecular tools and spatial analysis techniques. Isolates (n = 196) obtained from TB-like lesions (n = 200) were characterized by polymerase chain reaction. The isolates were positive to either M. bovis (IS6110) (n = 160) or M. avium (IS1245) (n = 16) while the remaining 20 (10.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…On the other hand, previous studies carried out also in Buenos Aires Province, but not in the exact region of this study, reported mycobacterioses in pigs caused by MAC. In that study, most of the cases were caused by MAA (n: 30) instead of MAH (n: 6) [14]. However, although it has been postulated the possible zoonotic role of MAH, the INMV patterns found for MAH isolates from pigs in Buenos Aires Province, were different from those found in the present study [14].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, previous studies carried out also in Buenos Aires Province, but not in the exact region of this study, reported mycobacterioses in pigs caused by MAC. In that study, most of the cases were caused by MAA (n: 30) instead of MAH (n: 6) [14]. However, although it has been postulated the possible zoonotic role of MAH, the INMV patterns found for MAH isolates from pigs in Buenos Aires Province, were different from those found in the present study [14].…”
Section: Discussioncontrasting
confidence: 81%
“…The four subspecies of M. avium are: (a) MAP that contains IS900 [7]; (b) M. avium subsp. avium (MAA), which contains IS901 and could affect humans [11][12][13][14]; (c) MAS (M. avium subsp. silvaticum) that also has IS901 [15]; and (d) M. avium subsp.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing Africa and Europe, the prevalence estimates may be influenced by the fact that the population density of pigs in Europe is much higher than in Africa [ 32 ], therefore Europe could be investing more resources in monitoring TB or in other trade-relevant disease in this species that enables TB suspicion and confirmation. However, South America, which shows on most of the sub-continent values of pig population density similar to those found in Africa [ 32 ], has an estimate which clearly weights data from two studies [ 41 , 42 ], both from Argentina. A single occurrence in Asia was retrieved in which the prevalence is 1.26%.…”
Section: Resultsmentioning
confidence: 58%
“…Furthermore, extensive information on swine leukocyte antigens is available and it is possible to predict cytotoxic T cell epitopes. Like humans, swine are a natural host to Mycobacterium species [ 54 ] and wild boar and free-range pigs can be infected by Mycobacterium tuberculosis complex and contribute to the spread of bovine tuberculosis [ 55 ]. Swine develop similar pathological lesions to those seen in humans following M .…”
Section: Discussionmentioning
confidence: 99%